Trends in extreme rainfall and temperature indices in the western Thailand. (25th November 2013) - Sharma, Devesh; Babel, Mukand Singh
ABSTRACT Trends in extreme daily temperature and rainfall have been analysed from 1961 to 2002 for the western Thailand (Mae Ping and Mae Klong river basins). Daily precipitation, maximum and minimum temperature data for 15 stations were analysed to calculate 21 extreme indices. The magnitude of trends was estimated using the linear regression method while its statistical significance was evaluated using the p‐value at 5% significance level and Kendall‐tau test. The result of the analysis depicts significant increase in the annual number of warm days and warm nights, with corresponding significant decreases in the annual number of cool days and cold nights. The warm spell duration indicator presents statistical rising trends. The trends for temperature indices are more consistent in the region compared to precipitation indices. There is insignificant decrease in annual total precipitation for nearly all stations. The maximum number of consecutive dry days (rain less than 1 mm) is increasing. The number of days with rainfall more than 10 and 20 mm has declined over both basins except at Kanchanaburi station. Analysis also reveals that there is less spatial coherent in other extreme indicators, namely, maximum 1‐day and 5‐days rainfall amount and simple daily intensity index.